2018
DOI: 10.1097/md.0000000000010967
|View full text |Cite
|
Sign up to set email alerts
|

Level of uric acid and uric acid/creatinine ratios in correlation with stage of Parkinson disease

Abstract: This study aims to investigate relationship between the level of uric acid (UA) and UA/creatinine ratios (UA/Cr) to the stage of Parkinson disease (PD).A total of 120 cases of PD patients who were admitted in our hospital between 2013 and 2015 were enrolled into this study; these 120 cases of PD patients were divided into 3 groups, according to Hoehn–Yahr (H-Y) classification: early stage (1–2 classification), medium stage (2.5–3 classification), and advanced stage (4–5 classification); UA and UA/Cr level in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
3
21
1
Order By: Relevance
“…We were unable to find evidence in support of the recent finding in a smaller sample (Zhong et al 2018) of a relationship between HY stage and UA levels. This may reflect other differences between the studies; our sample was generally less severe, with no patients of HY stage greater than 3, and untreated.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We were unable to find evidence in support of the recent finding in a smaller sample (Zhong et al 2018) of a relationship between HY stage and UA levels. This may reflect other differences between the studies; our sample was generally less severe, with no patients of HY stage greater than 3, and untreated.…”
Section: Discussioncontrasting
confidence: 99%
“…This may reflect other differences between the studies; our sample was generally less severe, with no patients of HY stage greater than 3, and untreated. Another study of 80 PD patients also showed greater reduction in UA with disease severity and, in contrast to Zhong et al (2018), with levodopa treatment (Vieru et al 2016).…”
Section: Discussionmentioning
confidence: 89%
“…This condition induces gout and accelerates the progression of renal and cardiovascular diseases [13]. On the other hand, UA exerts antioxidant activity in our body and many reports have shown a correlation between UA levels and reduced risk or favorable progression of neurogenerative diseases [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Homocysteine, uric acid (UA), albumin, and bilirubin are defined as laboratory parameters associated with oxidative stress. Low UA, albumin, and bilirubin concentrations were associated with many neurodegenerative diseases, including PD, but these changes in their concentrations as oxidative stress markers were not clarified as to whether they caused neurodegenerative diseases or they were results of the underlying process in the literature (7,17,18,19,20,21,22). Several studies showed that there was a correlation between hypoalbuminemia and increased CRP concentrations and other acute phase proteins (34).…”
Section: Discussionmentioning
confidence: 99%
“…toxins, free radicals, dysfunctions in the ubiquitin/proteasome system) can lead dopaminergic cells to undergo apoptotic death (8,9). Serum C-reactive protein (CRP) and albumin concentrations have recently been used as markers of systemic inflammation and oxidative stress in different diseases (7,10,11,12,13,14,15,16,17,18,19,20,21,22).…”
Section: Introductionmentioning
confidence: 99%